TEMPAT PERSALINAN DAN KONSELING SELAMA ANTENATAL CARE DI KABUPATEN TIMOR TENGAH SELATAN PROVINSI NUSA TENGGARA TIMUR - , Mariana Oni Betan, Prof. dr. Sulchan Sofoewan, SpOG(K), PhD. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Maternal mortality ratio in Timor Tengah Selatan District tends to fluctuate which in 2007 it was 502.7 per 100,000 live births and in 2008 it increased to 690.1 per 100,000 live births, and it decreased again in 2009 to 538.7 per 100,000 live births. Efforts to reduce mortality in this district have been done with increased deliveries in health facilities. Delivery assistance in health facilities starts from Antenatal Care (ANC) visits where women receive counseling about safe delivery. ANC visit coverage in the district is recorded 91% of 1 st visit and 59% of 4 th visit, while deliveries in health facilities have reached 61%. Objective: To determine whether women who receive counseling during ANC will choose to give birth in a health facility in Timor Tengah Selatan District. Methods: The study used a matched case-control design. Its population was women who gave birth during the year 2011. The research sample was all women who gave birth to the last child in the period of October 1 to December 31, 2011 that met the criteria for inclusion and exclusion as many as 102 people. Data analysis used the McNemar and conditional logistic regression test with Confidence Interval (CI) 95% and Î± 0.05. Results: Multivarible analysis showed counseling during ANC had a significant relationship to the place of delivery indicated by p value <0.05 and OR = 20.93 (95% CI 2.32 â 188.95). If did not receive counseling during ANC, low maternal education, long travel to the nearest health facility and husband or family as decision makers, the opportunity to deliver in non-health facility was higher. Conclusion: There was a significant relationship between counseling during ANC and place of delivery. Opportunities to give birth in non-health facilities were higher in women who did not receive counseling during ANC compared with those who received counseling.